Characterization of the Components and Pharmacological Effects of Mountain-Cultivated Ginseng and Garden Ginseng Based on the Integrative Pharmacology Strategy - Li, Sen; Wang, Ping; Yang, Wenzhi; Zhao, Chunhui; Zhang, Luoqi; Zhang, Jingbo; Qin, Yuewen; Xu, Haiyu; Huang, Luqi (Frontiers in Pharmacology, 2021)
Panax ginseng C. A. Mey. (PGCAM) is a herbaceous perennial belonging to the Araliaceae family. We aimed to establish a rapid, accurate and effective method to distinguish 15-year-old mountain-cultivated PGCAM (MCG) and garden-cultivated PGCAM (GG) using ultra-performance liquid chromatography-quadrupole time-of-flight-tandem mass spectrometry (UPLC-QTOF-MS/MS). We also explored the pharmacological mechanisms of the main components using the Integrative Pharmacology-based Network Computational Research Platform of Traditional Chinese Medicine (TCMIP V2.0; http://www.tcmip.cn/). Altogether, 24 chemical components were characterized to distinguish 15-year-old MCG and GG, including ginsenosides Ra2, Rg1, and Ra1, and malonyl-ginsenoside Ra3, etc.. The contents of 20 constituents (mainly protopanaxadiol-type) were higher in MCG compared with that in GG, and four constituents (mainly carbohydrate compounds) were higher in GG. A total of 105 putative targets were predicated based on identified compounds using TTFM of TCMIP v2.0. Moreover, 30 pathways involved by the 105 genes were identified based on Database for Annotation, Visualization and Integrated Discovery (DAVID) v6.7. Functionally, these putative targets were significantly involved in 30 pathways, which were divided into 10 models, including immune regulation, systems (metabolic, nervous, cardiovascular, reproductive), blood-pressure regulation, as well as antitumor, antiaging, antibacterial and anti-inflammatory effects. More importantly, the in vitro experimental validation confirmed that potential quality markers of MCG and GG can regulate the mRNA expression of PSA, S6K, MDM2 and p53 genes by acting on AR, mTOR, PI3K and other targets, and thus suppressing the proliferation of breast cancer. The Integrative Pharmacology Strategy may provide an efficient way to identify chemical constituents and explore the pharmacological actions of TCM formulations.